2011
DOI: 10.1002/pat.1624
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into synergistic effects of rare earth oxides on intumescent flame retardancy of polypropylene/poly (octylene‐co‐ethylene) blends

Abstract: Synergistic effects of two kinds of rare earth oxides (REOs), neodymium oxide (Nd2O3) or lanthanum oxide (La2O3) on the intumescent flame retardancy of thermoplastic polyolefin (TPO) made by polypropylene/poly (octylene‐co‐ethylene) blends were investigated systemically by various methods. The limiting oxygen index (LOI) of flame retardant TPO (FRTPO) filled by 30 wt% intumescent flame retardants (IFR) composed of ammonium polyphosphate (APP) and pentaerythritol (PER) has been increased from 30 to 32.5 and 33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…PPR has proved to exhibit more effective carbonization and a higher degree of graphitic network than that of free β-CD. A c c e p t e d M a n u s c r i p t 22 As far as starch is concerned, Wu and coworkers [93] prepared biodegradable PVA/glycerolplasticized thermoplastic starch (TPS) and then blended it with microencapsulated APP (MCAPP).…”
Section: Page 21 Of 127mentioning
confidence: 99%
“…PPR has proved to exhibit more effective carbonization and a higher degree of graphitic network than that of free β-CD. A c c e p t e d M a n u s c r i p t 22 As far as starch is concerned, Wu and coworkers [93] prepared biodegradable PVA/glycerolplasticized thermoplastic starch (TPS) and then blended it with microencapsulated APP (MCAPP).…”
Section: Page 21 Of 127mentioning
confidence: 99%
“…To solve these problems, researchers have made great efforts to develop oligomeric or polymeric IFRs with relatively higher molecular weight and synergistic agent have been sued to enhance the flame retardancy of IFR [11][12][13][14]. The previous studies showed that some silicon-containing compounds, boron-containing compound, transitional metal oxides, 4A zeotile, metal compounds could serve as synergistic agents to increase the strength and stability of char layer to enhance the flame retardant performance of the composites [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…The most researches about synergistic effect focused on the traditional IFR systems containing ammonium polyphosphate (APP)/ pentaerythritol (PER) or other char forming agent containing hydroxyl group [15][16][17][18][19][20][21][22][23]. However, the presentation of hydroxyl group in the IFR would deteriorate compatibility between the flame retardants and the matrix and increase the moisture sensitivity of the composites.…”
Section: Introductionmentioning
confidence: 98%
“…In this case, rare earth based-compounds may be a promising synergist for IFR to promote the formation of carbonaceous materials. Ren et al [19] investigated the synergistic effects of neodymium oxide (Nd 2 O 3 ) and lanthanum oxide (La 2 O 3 ) on the intumescent flame retardancy of polypropylene/poly (octyleneco-ethylene) blends filled by 30 wt% IFR composed of APP and PER. They found that the limiting oxygen index (LOI) of the blends has been increased from 30 to 32.5 and 33.5 when 0.5 wt% of IFR was substituted by La 2 O 3 and Nd 2 O 3 , respectively.…”
Section: Introductionmentioning
confidence: 99%